Effect of cock’s comb extract in the treatment of palmar arsenical keratosis (Bangladesh Journal of Pharmacology, 2019)
The aim of this study was to examine the effect of cock’s comb extract in the treatment of moderate palmar arsenical keratosis (n = 35). All the patients were provided cock’s comb extract ointment to apply topically twice daily for 12 weeks. Adherence to the ointment and adverse effects were monitored regularly through the phone call and during the visit of each patient. Photographs of both palms were collected before and after treatment. Clinical improvement was assessed by measuring the arsenical keratotic nodular size of the both palms before starting the treatment and after completion of the treatment. The mean (± SD) sizes of the nodules before the study was 33.6 ± 16.8, which reduced to 5.4 ± 5.2 after completion of the study. This change (84% reduction) was statistically significant. None of the patients reported to any adverse effect during this study period. In conclusion, cock’s comb extract can be used effectively as a topical treatment of the palmar arsenical keratosis.